INTENTION TO DONATE KIDNEY IN INDONESIA: THE ROLE OF FINANCIAL INCENTIVE, PERCEIVED RISK, AND ALTRUISM - Elsa Adelia Nurrachma; Budhi Haryanto; Nurmadi Harsa Sumarta (Universitas Mercu Buana, 2018)
This study aims to explore individual motivations to donate kidney in the context of humanity-oriented marketing. It was aimed to understand the influences of financial incentive and perceived risk in the decision of donating kidney. This study tried to specify the kidney donors into altruistic and unrelated kidney donor type, where previous study tends to generalize the behavior of all kidney sources. This study also tries to test the moderating role of altruism, because kidney donation is an act that’s driven by humanity values. Using non-probability sampling, survey method with online questionnaires, the samples consist of 101 out of 125 obtained data from 545 contacted potential donors in Kidney Donor Indonesia Facebook community. To analyze the data, this study use Structural Equation Modeling with Smart Partial Least Square (PLS) 3 Software. The result indicates that altruism moderates the behavior of kidney donors because the consideration of kidney donor’s in high and low altruism group found to have differences. Health authorities and related institutions that runs the kidney donation program can use the presented findings to create a better strategy in promoting kidney donation and increasing the awareness of potential market in Indonesia. Further, to understood the perception and consideration of kidney donor in donating their organ